Ecography_ECOG-02995_DRYAD_2017 - Ortego, Joaquin; Yannic, Glenn; Lecomte, Nicolas; Pellissier, Loïc; Bernatchez, Louis; Côté, Steeve (Dryad Digital Repository, 2017)
Table Dryad 1. Sampling sites, number of individuals genotyped at 16 nuclear microsatellites (N), Census population size, and environmental variables for each population (n=57). Table Dryad 2. Pairwise genetic differentiation between caribou herds. Below diagonal: Fst and above diagonal: Dc chord distance. Table Dryad 3. Pairwise geographic distance (IBD) between caribou herds. Below diagonal: geodesic distance and above diagonal: distance on a flat landscape. Table Dryad 4. Above diagonal: Pairwise environmental dissimilarity (IBE) between caribou herds. Below diagonal: Pairwise landscape resistance (IBR) between caribou herds Table Dryad 5. Pairwise harmonic mean of census population sizes (Nc)